(Invited) Requirements for Highly Accurate Multiphysics Modeling of SiC Power MOSFETs and Power Modules. (17th August 2017) - Grossner, Ulrike; Kakarla, Bhagyalakshmi; Ziemann, Thomas; Muting, Johanna; Stark, R.; Kovacevic-Badstuebner, Ivana
Abstract : Highly accurate modeling of Silicon Carbide (SiC) Power MOSFTEs and their packages represents the basis for virtual prototyping of emerging SiC power devices. The main aim of virtual prototyping is to gain a comprehensive physical understanding of the electro-thermal behavior of SiC power MOSFETs and as well as of the influence of parasitic inductive, capacitive and resistive elements of power modules on the actual dynamic performance of SiC devices without any hardware prototyping. A modeling approach based on linking the results from state-of-the-art commercial multi-domain tools to circuit simulators is presented demonstrating the challenges of developing accurate and fast multi-physics modeling environments, which will enable virtual prototyping of advanced all-SiC power electronics systems with optimized performance.